Evaluation of biocidal properties of biodegradable nanofiber filters and their use in face masks. Issue 5 (23rd February 2023) - de Almeida, Daniela S.; Scacchetti, Fabio A. P.; Santos, Roberta; Aguiar, Monica Lopes; Beal, Alexandra; Rudke, Anderson P.; Santana, Marcos Henrique de Souza; Lisboa, Ana Maria Valério; Bezerra, Fabricio M.; Martins, Leila D.
ABSTRACT: Due to the recent coronavirus-2019 pandemic, several studies have emerged looking for new materials, especially with biocidal characteristics. Thus, the present research investigates the antibacterial properties of biodegradable cellulose acetate (CA) / cetylpyridinium bromide (CPB) electrospun nanofibers, their aerosol filtration, and the possible use as a filter media of surgical face masks. Then, samples of these nanofibers were produced over a nonwoven substrate, using different volumes of polymeric solution during the electrospinning process. The evaluation of the antibacterial properties of the nanofibers was performed for Escherichia coli and Staphylococcus aureus using quantitative methods. The aerosol filtration performance was evaluated in these samples for NaCl nanoparticles (from 7-300 nm) and with 8 mL min −1 of air flow rate. The results show that the single use of the surfactant has antibacterial properties from a concentration of 39 µg mL −1 of solution. The nanofibers presented a reduction of 100% for both bacteria. Air filtration tests showed 126.03 and 207.73 Pa cm − ² of pressure drops and 63 and 77% of aerosol filtration efficiency (FE) for samples with 0.13 and 0.15 mL, respectively. Regarding the nanofiber produced with 0.35 mL, the value obtained was 115.13 ± 33.64 Pa cm −2 and 3.15% of particle penetration. These breathability values are higher than those required for the surgical face mask standard, indicating that improvements in the porosity and thickness are necessary to meet the Brazilian requirements. However, the nanofibers could be applied as filter media for indoor air conditioning systems due to their FE and biocidal properties. GRAPHICAL ABSTRACT: UF0001